Defect-rich nano-porous Co-P material as well as preparation method and application thereof

Defectively rich nanoporous Co-P materials are prepared by dealloyment method and ball milling method, which solves the problems of high cost of platinum-based catalysts and traditional phosphide preparation methods, and achieves a nanoporous structure with high catalytic activity and stability, suitable for electrolysis Aquatic hydrogen catalysts significantly improve catalytic performance.

CN119221010APending Publication Date: 2024-12-31TIANJIN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411138705.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-19
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing platinum-based catalysts are costly to prepare during electrolytic hydrogen analysis, which limits the large-scale application of electrolytic water devices. The reaction rate is not easy to regulate during the doping process of harmful gases and non-metallic elements.

Method used

Defective nanoporous Co-P materials are prepared by dealloyment method and ball milling method. Defective structures are introduced to improve catalytic activity through ultrasonic treatment, ball milling and hydrochloric acid insulation reactions, avoid the generation of waste gas in the vapor deposition method and regulate the electronic structure of the catalyst. .

Benefits of technology

Defective nanoporous Co-P materials with high catalytic activity, stability and conductivity are obtained, which can exhibit high current density during electrolysis of aquatic hydrogen. They are suitable for cathode catalysts for electrolysis of aquatic hydrogen, significantly improving the performance of the catalyst and Application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119221010A_ABST
    Figure CN119221010A_ABST
Patent Text Reader

Abstract

The invention discloses a defect-rich nano-porous Co-P material as well as a preparation method and application thereof. The defect-rich nano-porous Co-P material prepared by using hydrochloric acid and a Co-P alloy dealloying method has a nano-porous structure with bicontinuous pore channels and pore walls, and the material has high specific surface area, good conductivity and high stability and can promote substance transport. Due to modulation of local electrons and surface configuration, defects are usually considered to be active sites in the electro-catalysis process. Vacancy, dislocation and other defect structures are introduced into the transition metal phosphide, through the synergistic effect of multiple defect sites, the electronic structure of catalyst active sites is effectively regulated and controlled, formation and transformation of reaction intermediates are promoted, and therefore the water electrolysis hydrogen evolution reaction is promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of nanomaterials, and in particular to a defect-rich nanoporous Co-P material and a preparation method and application thereof. Background Art

[0002] As an ideal secondary energy carrier, hydrogen has a high unit energy density and is an ideal interconnected medium to promote clean and efficient utilization and support the large-scale development of renewable energy. At present, platinum-based catalysts are still the best performing hydrogen evolution catalysts for water electrolysis, but their high preparation costs limit the large-scale application of water electrolysis devices. Transition metal phosphides such as Co-P alloys have good structural stability, thermal and electrical conductivity, and thermodynamic stability, and are considered to be ideal materials to replace precious metal catalysts.

[0003] In recent years, crystal defect theory has received extensive attention in the field of electrocatalysis, and defect engineering has been widely used in the preparation of various catalysts and various catalytic reactions. Due to the modulation of localized electrons and surface configurations, the defect positions of catalysts usually exhibit special electronic properties, have good activation ability for reaction intermediates, and are considered to be active sites in the electrocatalytic process. High-energy ball milling has many advantages such as simple operation, rich structural changes that can be induced, uniform products, high surface activity, and easy large-scale preparation. It is a very promising method for catalyst structure regulation. Conventional phosphide preparation methods mainly use vapor deposition and other means to phosphide metal compound precursors, which will produce harmful gases during the preparation process. The dealloying method can add non-metallic elements to the precursor alloy by smelting, which can effectively avoid the generation of waste gas during the doping process of non-metallic elements and the problem that the reaction rate of non-metallic sources is difficult to control. Therefore, choosing an appropriate method to prepare defect-rich nanoporous Co-P material catalysts can maximize the catalytic activity of phosphide catalysts. Summary of the invention

[0004] In order to solve the deficiencies of the above technical solutions, the object of the present invention is to provide a method for preparing defect-rich nanoporous Co-P material.

[0005] Another object of the present invention is to provide a defect-rich nanoporous Co-P material obtained by the above preparation method.

[0006] Another object of the present invention is to provide an application of the above defect-rich nanoporous Co-P material in a cathode catalyst for hydrogen production by water electrolysis.

[0007] The purpose of the present invention is achieved through the following technical solutions.

[0008] A method for preparing defect-rich nanoporous Co-P material comprises the following steps:

[0009] Step 1, placing the Co-P alloy in anhydrous ethanol for ultrasonic treatment, washing it with deionized water, taking it out and drying it to obtain a pretreated Co-P alloy, wherein the atomic ratio of Co to P in the Co-P alloy is (70-90): (10-30);

[0010] Step 2, in a nitrogen atmosphere, ball-milling the pretreated Co-P alloy, taking it out, washing it with deionized water, and drying it to obtain a dried Co-P alloy;

[0011] Step 3, after the dried Co-P alloy is mixed with hydrochloric acid, it is placed in a closed container and subjected to a heat preservation reaction at 20 to 70°C, and the product obtained after the heat preservation reaction is washed with deionized water and dried to obtain a defect-rich nanoporous Co-P material, wherein the ratio of the mass fraction of the dried Co-P alloy to the volume fraction of the hydrochloric acid is (10 to 100): (50 to 200), the unit of the mass fraction is mg, and the unit of the volume fraction is ml.

[0012] In the above technical solution, in step 1, the Co-P alloy is cut into alloy strips with a thickness of 10 to 30 μm, a width of 15 to 20 mm, and a length of 1 to 3 cm, and then placed in anhydrous ethanol for ultrasonic treatment.

[0013] In the above technical solution, in step 1, the time used for the ultrasound is 5 to 30 minutes.

[0014] In the above technical solution, in step 1, the drying is carried out in air.

[0015] In the above technical solution, in step 2, the ball milling time is 1 to 72 hours.

[0016] In the above technical solution, in step 2, the drying is carried out in a vacuum drying oven.

[0017] In the above technical solution, in step 3, the molar concentration of the hydrochloric acid is 0.5 to 3M.

[0018] In the above technical solution, in step 3, the insulation reaction time is 12 to 36 hours.

[0019] Another aspect of the present invention also includes the defect-rich nanoporous Co-P material obtained by the above preparation method.

[0020] Another aspect of the present invention also includes the use of the defect-rich nanoporous Co-P material as a cathode catalyst for hydrogen production by water electrolysis. The current density of the defect-rich nanoporous Co-P material for electrocatalytic hydrogen production at an overpotential of -0.2V is 67.69 mA / cm 2 .

[0021] The advantages and beneficial effects of the present invention are:

[0022] 1. The defect-rich nanoporous Co-P material prepared by the dealloying method of hydrochloric acid and Co-P alloy in the present invention has a nanoporous structure with bicontinuous pores and pore walls. Such materials have high specific surface area, good electrical conductivity and high stability and can promote material transport. Defects are generally considered to be active sites in electrocatalytic processes due to the modulation of localized electrons and surface configurations. Defect structures such as vacancies and dislocations are introduced into transition metal phosphides. Through the synergistic effect of multiple defect sites, the electronic structure of the active sites of the catalyst is effectively regulated, and the formation and transformation of reaction intermediates are promoted, thereby promoting the electrolysis of water and hydrogen evolution reaction.

[0023] 2. The defect-rich nanoporous Co-P material prepared by the ball milling method and the dealloying method has a stable nanoporous structure and a current density of 67.69 mA / cm2 for electrocatalytic hydrogen production at an overpotential of 200 mV in a linear sweep voltammetry test. 2 .

[0024] 3. The defect-rich nanoporous Co-P material of the present invention shows an obvious hydrogen evolution current in the linear sweep voltammetry test, indicating that the material has a good application prospect in the field of hydrogen production by water electrolysis.

[0025] 4. During the ball milling process of step 2 of the present invention, the mechanical energy generated by the impact force, shear force, pressure and other forces can be continuously transferred and converted into the pretreated Co-P alloy lattice, so that the energy of the Co-P alloy system is increased and tends to produce a large number of vacancy, dislocation, lattice distortion and other lattice defects. Due to the modulation of localized electrons and surface configurations, the defect positions of Co-P alloy materials usually show special electronic properties, which can enhance the catalytic activity of Co-P alloy materials. Therefore, defects can be introduced into the Co-P alloy through the ball milling process in step 2, and the Co-P alloy after ball milling has a uniform size and a particle size of about 100 μm. While the introduction of mechanical energy in the traditional ball milling process will inevitably damage the nanostructure of the material, the spatial confinement effect of the metal nanocrystals in the Co-P alloy on the phosphide nanocrystals can ensure that the Co-P alloy crystals produce crystal defects during the ball milling process while maintaining a small grain size. Utilizing the characteristics of Co-P nanocrystals having a higher chemical stability than metal cobalt nanocrystals, a well-structured defect-rich nanoporous Co-P material can be obtained through the dealloying process in step 3. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a schematic diagram of the process of the present invention.

[0027] Figure 2These are SEM images of the surface nanoporous structures of defect-rich nanoporous Co-P materials prepared in Examples 1 to 4, where (a) is Example 1, (b) is Example 2, (c) is Example 3, and (d) is Example 4.

[0028] Figure 3 Linear sweep voltammetry curves of defect-rich nanoporous Co-P materials prepared in Examples 1 to 4. DETAILED DESCRIPTION

[0029] The technical solution of the present invention is further described below in conjunction with specific embodiments.

[0030] Example 1

[0031] A method for preparing defect-rich nanoporous Co-P material comprises the following steps:

[0032] like Figure 1 As shown, step 1, Co-P alloy (Co 80 P 20 The pretreated Co-P alloy is cut into alloy strips with a thickness of 10 to 30 μm, a width of 15 to 20 mm, and a length of 1 to 3 cm, and then placed in anhydrous ethanol for ultrasonic treatment for 5 minutes, and cleaned with deionized water, and then taken out and dried in air to obtain a pretreated Co-P alloy, wherein the atomic ratio of Co to P in the Co-P alloy is 80:20.

[0033] Step 2: In a nitrogen atmosphere, the pretreated Co-P alloy is ball-milled for 48 hours, taken out, washed with deionized water, and dried in a vacuum drying oven to obtain a dried Co-P alloy.

[0034] Step 3, 0.1 g of the dried Co-P alloy is mixed with 100 ml of 1 M hydrochloric acid, placed in a sealed container, and placed in a drying oven for heat preservation reaction at 20° C. for 12 hours, and the product obtained after the heat preservation reaction is washed with deionized water and dried in air to obtain a defect-rich nanoporous Co-P material.

[0035] Example 2

[0036] A method for preparing defect-rich nanoporous Co-P material comprises the following steps:

[0037] Step 1: Co-P alloy (Co 70 P 30 The alloy is cut into alloy strips with a thickness of 10 to 30 μm, a width of 15 to 20 mm, and a length of 1 to 3 cm, and then placed in anhydrous ethanol for ultrasonic treatment for 5 minutes, and cleaned with deionized water, and then taken out and dried in air to obtain a pretreated Co-P alloy, wherein the atomic ratio of Co to P in the Co-P alloy is 70:30.

[0038] Step 2: In a nitrogen atmosphere, the pretreated Co-P alloy is ball-milled for 24 hours, taken out, washed with deionized water, and dried in a vacuum drying oven to obtain a dried Co-P alloy.

[0039] Step 3, 0.1 g of the dried Co-P alloy is mixed with 100 ml of 0.5 M hydrochloric acid, placed in a sealed container, and placed in a drying oven for heat preservation at 50° C. for 24 hours. The product obtained after the heat preservation reaction is washed with deionized water and dried in air to obtain a defect-rich nanoporous Co-P material.

[0040] Example 3

[0041] A method for preparing defect-rich nanoporous Co-P material comprises the following steps:

[0042] Step 1: Co-P alloy (Co 85 P 15 The alloy is cut into alloy strips with a thickness of 10 to 30 μm, a width of 15 to 20 mm, and a length of 1 to 3 cm, and then placed in anhydrous ethanol for ultrasonic treatment for 5 minutes, and cleaned with deionized water, and then taken out and dried in air to obtain a pretreated Co-P alloy, wherein the atomic ratio of Co to P in the Co-P alloy is 85:15.

[0043] Step 2: In a nitrogen atmosphere, the pretreated Co-P alloy is ball-milled for 12 hours, taken out, washed with deionized water, and dried in a vacuum drying oven to obtain a dried Co-P alloy.

[0044] Step 3, 0.1 g of the dried Co-P alloy is mixed with 100 ml of 2M hydrochloric acid, placed in a sealed container, and placed in a drying oven for heat preservation at 30°C for 24 hours, and the product obtained after the heat preservation reaction is washed with deionized water and dried in air to obtain a defect-rich nanoporous Co-P material.

[0045] Example 4

[0046] A method for preparing defect-rich nanoporous Co-P material comprises the following steps:

[0047] Step 1: Co-P alloy (Co 90 P 10 The alloy is cut into alloy strips with a thickness of 10 to 30 μm, a width of 15 to 20 mm, and a length of 1 to 3 cm, and then placed in anhydrous ethanol for ultrasonic treatment for 5 minutes, and cleaned with deionized water, and then taken out and dried in air to obtain a pretreated Co-P alloy, wherein the atomic ratio of Co to P in the Co-P alloy is 90:10.

[0048] Step 2: In a nitrogen atmosphere, the pretreated Co-P alloy is ball-milled for 72 hours, taken out, washed with deionized water, and dried in a vacuum drying oven to obtain a dried Co-P alloy.

[0049] Step 3, 0.1 g of the dried Co-P alloy is mixed with 100 ml of 3M hydrochloric acid, placed in a sealed container, and placed in a drying oven for heat preservation reaction at 70°C for 36 hours, and the product obtained after the heat preservation reaction is washed with deionized water and dried in air to obtain a defect-rich nanoporous Co-P material.

[0050] Comparative Example

[0051] A method for preparing a defect-free Co-P material is provided, wherein the defect-free Co-P material is prepared by steps 1 and 3 in embodiment 1.

[0052] like Figure 2 The SEM images of defect-rich nanoporous Co-P materials prepared in Examples 1 to 4 are shown. Figure 1 It can be seen that the pore wall and pore size of the defect-rich nanoporous Co-P material are regulated by alloy composition and ball milling process, and the pore wall and pore size are about 20-100nm, indicating that it has a smaller nanostructure and therefore has a high specific surface area. This bicontinuous nanoporous structure with continuous pore walls and pores has good electrical conductivity and high stability and can promote material transport, so it has good application prospects in the preparation of water electrolysis hydrogen production catalysts.

[0053] Depend on Figure 3 It can be seen that compared with the defect-free Co-P material in the comparative example, the defect-rich nanoporous Co-P material has stable chemical properties and more unsaturated coordinated atoms. In the linear sweep voltammetry test, the current density of electrocatalytic hydrogen production at a reaction potential of -0.2 V can reach 67.69 mA / cm 2 .

[0054] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.

Claims

1. A method for preparing defect-rich nanoporous Co-P material, characterized in that: The following steps are involved: Step 1, placing the Co-P alloy in anhydrous ethanol for ultrasonic treatment, washing it with deionized water, taking it out and drying it to obtain a pretreated Co-P alloy, wherein the atomic ratio of Co to P in the Co-P alloy is (70-90): (10-30); Step 2, ball-milling the pretreated Co-P alloy in a nitrogen atmosphere, taking it out, washing it with deionized water, and drying it to obtain a dried Co-P alloy; Step 3, after the dried Co-P alloy is mixed with hydrochloric acid, it is placed in a closed container and subjected to a heat preservation reaction at 20 to 70°C, and the product obtained after the heat preservation reaction is washed with deionized water and dried to obtain a defect-rich nanoporous Co-P material, wherein the ratio of the mass fraction of the dried Co-P alloy to the volume fraction of the hydrochloric acid is (10 to 100): (50 to 200), the unit of the mass fraction is mg, and the unit of the volume fraction is ml.

2. The preparation method according to claim 1, characterized in that: In the step 1, the Co-P alloy is cut into alloy strips with a thickness of 10 to 30 μm, a width of 15 to 20 mm, and a length of 1 to 3 cm, and then placed in anhydrous ethanol for ultrasonic treatment.

3. The preparation method according to claim 1, characterized in that: In the step 1, the ultrasonic treatment takes 5 to 30 minutes.

4. The preparation method according to claim 1, characterized in that: In the step 1, the drying is performed in air.

5. The preparation method according to claim 1, characterized in that: In the step 2, the ball milling time is 1 to 72 hours.

6. The preparation method according to claim 1, characterized in that: In the step 2, the drying is carried out in a vacuum drying oven.

7. The preparation method according to claim 1, characterized in that: In step 3, the molar concentration of the hydrochloric acid is 0.5 to 3M.

8. The preparation method according to claim 1, characterized in that: In step 3, the insulation reaction time is 12 to 36 hours. 9 . The defect-rich nanoporous Co-P material obtained by the preparation method according to claim 1 .

10. The use of the defect-rich nanoporous Co-P material as claimed in claim 9 in a cathode catalyst for producing hydrogen by electrolysis of water, characterized in that: The current density of electrocatalytic hydrogen production of defect-rich nanoporous Co-P material at an overpotential of -0.2 V is 67.69 mA / cm 2 .